2019
DOI: 10.1002/hbm.24858
|View full text |Cite
|
Sign up to set email alerts
|

Linking brain structure and activation in anterior insula cortex to explain the trait empathy for pain

Abstract: The ability to perceive, understand, and react to the feelings of others' pain is referred to as empathy for pain which is composed of two components, affectiveperceptual empathy and cognitive-evaluative empathy. Recent reviews on the neural mechanisms of empathetic pain showed the anterior insula (AI) cortex as a core circuit for empathy. However, little is known about the modulation of brain anatomy and empathic responses by trait measures of empathy (trait empathy). Thus, we investigated whether individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 73 publications
(144 reference statements)
0
16
3
Order By: Relevance
“…In addition, neural regions previously associated both with empathy for pain and with reappraisal (e.g. anterior and posterior regions of the left SMG within the IPL as well as the parietal operculum—empathy for pain: Costantini et al., 2008 ; Li et al., 2019 ; Morawetz et al., 2015 ) were involved when participants employed reappraisal following exposure to painful scenarios. A gPPI analysis revealed increased functional connectivity between the right IFG and regions of the network involved in empathy for pain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neural regions previously associated both with empathy for pain and with reappraisal (e.g. anterior and posterior regions of the left SMG within the IPL as well as the parietal operculum—empathy for pain: Costantini et al., 2008 ; Li et al., 2019 ; Morawetz et al., 2015 ) were involved when participants employed reappraisal following exposure to painful scenarios. A gPPI analysis revealed increased functional connectivity between the right IFG and regions of the network involved in empathy for pain.…”
Section: Discussionmentioning
confidence: 99%
“… 8 A neuroimaging study also showed that the IRI score was correlated with the neural activity in the bilateral anterior insula during state empathy for pain. 9 Therefore, the scale of IRI is a suitable measurement to reveal the trait empathy and the empathy for pain.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that observing others in pain and feeling pain yourself leads to considerable overlap in brain activation, for example in the bilateral anterior insulae (AI) and medial areas of the prefrontal cortex 30 32 . This overlap could indicate that we feel with the other person when we observe them in pain which is corroborated by correlations between activation in these areas and trait empathy or behavioural empathy ratings 30 , 33 36 . Empathy for pain paradigms investigate responses to other’s in pain and are open to influences of the perceiver 37 and the person in pain 38 , 39 .…”
Section: Introductionmentioning
confidence: 63%